(untitled) (Research, Society and Development, 2020)
Fibromyalgia is a syndrome that affects about 15% of patients, which manifests itself through pain throughout the body, especially in the muscles, bringing unrepaired muscle fatigue and sleep. The best strategy for managing fibromyalgia is to use a multidisciplinary approach to treatment using pharmacological and non-pharmacological interventions. This article aimed to address the new drugs for the treatment of fibromyalgia through a scientific and technological review in search of patents. The methodology used was a qualitative scientific review of the literature, consisting in the cataloging of data contained in electronic files. As inclusion criteria were considered the articles published between 2014 and 2019 that include the research descriptors, available in full on the internet with database Scielo, Bvs e Medline. Ten articles were cataloged that met the proposed objectives for their insertion in the present study. It was sought in the international network of patents and patent findings in the last 5 years with drugs to treat fibromyalgia. Fibromyalgia is a condition that affects a good part of the population, its treatment is quite complex because there are several drug classes. It can be inferred that new drugs are being studied every day to be used and contain fewer adverse effects in individuals with fibromyalgia.